STUDENT PERCEPTIONS OF DIFFICULTIES IN ACADEMIC WRITING COURSES - USMANOVA GULRUKH SHOKIRJONOVNA (International Journal of Innovations in Engineering Research and Technology, 2021)
This article is dedicated to the development of academic literacy, especially writing among students. It is based on the need to develop academic skills based on teaching reading and writing. In the process of developing academic literacy skills in English, the need for students to develop academic literacy in their mother tongue was emphasized. When learning a language, everyone faces challenges on different fronts. It is not always successful when learning English. It is obvious that it is extremely difficult to achieve an academic degree. In particular, in this article I would like to dwell on academic writing.